Simplify.
–(2x – 3y) + 5x + 2 – 3x + 3y + 2
A.
4
B.
4x + 4
C.
6y + 4
D.
4x + 6y + 4

Question

Asked 9/24/2013 5:44:55 AM

Updated 9/2/2014 3:23:16 AM

1 Answer/Comment

Question

Asked 9/24/2013 5:44:55 AM

Updated 9/2/2014 3:23:16 AM

1 Answer/Comment

Rating

3

–(2x – 3y) + 5x + 2 – 3x + 3y + 2

= -2x + 3y + 5x + 2 - 3x + 3y + 2

= (-2x + 5x - 3x) + (3y + 3y) + (2 + 2)

= 6y + 4

= -2x + 3y + 5x + 2 - 3x + 3y + 2

= (-2x + 5x - 3x) + (3y + 3y) + (2 + 2)

= 6y + 4

Added 9/2/2014 3:02:59 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/2/2014 3:23:04 AM]

27,085,327

questions answered

There are no comments.